Synthesis of activated carbon from cherry tree waste and its application in removing cationic red 14 dye from aqueous environments - Roya Askari; Faezeh Mohammadi; Amir Moharrami; Shirin Afshin; Yousef Rashtbari; Mehdi Vosoughi; Abdollah Dargahi (Applied Water Science, 2023)
Abstract The environment is threatened by a diversity of pollutants, and synthetic dyes are considered a foremost environmental pollutant among them. The characteristics detected for the dye, e.g., toxicity and carcinogenicity, have brought severe problems for humans and aquatic organisms. The present study was done to clarify the potential of activated carbon made from cherry tree wood (CWAC) in the adsorption of cationic red 14 dye. In our experimental-laboratory study, the changes in removal efficiency were assessed by considering the changes in values of pH, concentration, adsorbent dose, contact time, and temperature. In addition, the nature of our prepared adsorbent was defined based on scanning electron microscopy (SEM), Brunauer–Emmett–Teller (BET), X-ray diffraction (XRD), and Fourier-transformed infrared (FTIR) spectroscopy techniques. The concentration of dye after the completion of experiments was recorded using a spectrophotometer at 514 nm. Evaluating the attained data by isotherm and kinetic models were also considered. Our results demonstrated the enhancement in the efficiency of the studied process at higher contact times, temperatures, and pH and its decline at higher initial dye concentrations. pH = 11, time of 45 min, dye concentration of 50 mg/L, and AC mass of 0.25 g/l were optimal values in obtaining the highest removal of the studied dye. Langmuir isotherm and pseudo-second-order (PSO) with (R 2 = 0.9972) and (R 2 = 0.9947) were the best isotherms and kinetic models in the description of the observed data, respectively. Considering the results, CWAC could be effectively utilized for the adsorption of cationic red 14 dye from solutions.